Homocysteine and risk of age‐related macular degeneration: a systematic review and meta‐analysis - Pinna, Antonio; Zaccheddu, Francesco; Boscia, Francesco; Carru, Ciriaco; Solinas, Giuliana (Acta ophthalmologica (Oxford, England), 2018)
There is still no agreement on total plasma homocysteine (tHcy) role in age‐related macular degeneration (AMD), the leading cause of new blindness in industrialized countries. We performed a systematic review and meta‐analysis of the published data on the correlation between tHcy and AMD. MEDLINE/PubMed and ISI Web of Sciences searches were performed according to MOOSE guidelines. Case–control studies were eligible for inclusion. Participants and controls were AMD patients and subjects without AMD. The main outcome measure was wet AMD. Homocysteine level was the main exposure variable. Data were pooled using a random‐effects model. Twelve case–control studies were identified: 10 assessed wet AMD, four dry AMD, one early AMD, one late AMD, and one any AMD. As for wet AMD, there was a total of 453 cases and 514 controls. Mean tHcy was on average 1.1 μmol/l (95% confidence interval [CI] = 0.96–1.25) greater in wet AMD cases, but there was evidence of extreme between‐study heterogeneity (p < 0.001, I2 = 91.8%). In a model homogenous for age, including six wet AMD studies (214 cases, 274 controls), mean tHcy was on average 0.58 μmol/l (95% CI = 0.35–0.73) greater in the case group, a not statistically significant result (p = 0.144) associated with moderate heterogeneity (I2 = 39.2%). Our meta‐analysis indicates that there is some weak evidence that increased tHcy might be associated with wet AMD; however, this result should be interpreted cautiously, because of a marked between‐study heterogeneity and the possible effect of publication bias. Future studies, preferably of cohort design, are necessary before any firm conclusions on the putative role of increased tHcy on AMD can be drawn.